Randomised controlled trial of Alexander technique lessons, exercise, and massage (ATEAM) for chronic and recurrent back pain. (19th August 2008) - Little, Paul; Lewith, George; Webley, Fran; Evans, Maggie; Beattie, Angela; Middleton, Karen; Barnett, Jane; Ballard, Kathleen; Oxford, Frances; Smith, Peter; Yardley, Lucy; Hollinghurst, Sandra; et al.
Abstract : Objective To determine the effectiveness of lessons in the Alexander technique, massage therapy, and advice from a doctor to take exercise (exercise prescription) along with nurse delivered behavioural counselling for patients with chronic or recurrent back pain. Design Factorial randomised trial. Setting 64 general practices in England. Participants 579 patients with chronic or recurrent low back pain; 144 were randomised to normal care, 147 to massage, 144 to six Alexander technique lessons, and 144 to 24 Alexander technique lessons; half of each of these groups were randomised to exercise prescription. Interventions Normal care (control), six sessions of massage, six or 24 lessons on the Alexander technique, and prescription for exercise from a doctor with nurse delivered behavioural counselling. Main outcome measures Roland Morris disability score (number of activities impaired by pain) and number of days in pain. Results Exercise and lessons in the Alexander technique, but not massage, remained effective at one year (compared with control Roland disability score 8.1: massage −0.58, 95% confidence interval −1.94 to 0.77, six lessons −1.40, −2.77 to −0.03, 24 lessons −3.4, −4.76 to −2.03, and exercise −1.29, −2.25 to −0.34). Exercise after six lessons achieved 72% of the effect of 24 lessons alone (Roland disability score −2.98 and −4.14, respectively). Number of days with back pain in the past four weeks was lower after lessons (compared with control median 21 days: 24 lessons −18, six lessons −10, massage −7) and quality of life improved significantly. No significant harms were reported. Conclusions One to one lessons in the Alexander technique from registered teachers have long term benefits for patients with chronic back pain. Six lessons followed by exercise prescription were nearly as effective as 24 lessons. Trial registration National Research Register N0028108728. How does the Alexander Technique work? What are the authors findings about the clinical and cost effectiveness of the treatment? Watch this video to find out (12 mins). media-1 10.1136/bmj.a884V1